Biological warfare canaries [biological attack detection]. - Aston, C.
A full-blown biological attack would come unannounced and spread inordinate disease and death. A bioattack could take days or weeks to surface, until enough illness and deaths have occurred for public health officials to realize what has happened. In this paper, the author describes new early-warning detectors which aim to avert such a catastrophe
Keywords: Bioattack; Biological attack detection; Death; Disease; Early-warning detectors; Illness; Public health